Aerial photo of Salinas - George Lawrence:::Creator::::::::::::
Aerial Panorama. Large railroad yard in the foreground, taking up almost half the picture. The picture was taken facing south, towards Mount Toro (left of center). To the right of center is Highway 68 disappearing between the hills heading west. The sun is setting, so the building facades facing west are more brightly illuminated than any other features in the picture. Lawrence usually took pictures from a camera height of 820 ft.( 250m.) to 984 ft. (300m,) although the lead kite would be above and higher, up to close to 2000 ft. (600m.). His film exposure was calibrated to the camera height, and he also used a shield over the lens to give more exposure to the distant background, and less exposure to the foreground. This picture was probably taken at 330 ft. (100m.). It appears that Lawrence took this picture in a hurry, at the end of the day, from a lower altitude than usual, and so the exposure is not up to his usual standard. The Steinbeck house can be seen from the back, partly obscured by a tree. This photograph is from the Library of Congress collection.